Potential mosquito larvicides from Morinda citrifolia root extract - Ee, Gwendoline Cheng Lian; Wen, Yin Ping; Bong, Joseph Choon Fah; Md. Sukari, Mohd. Aspollah (University of Malaya, 2009)
In our recent investigation on Morinda citrifolia as a potential larvicide against the larvae of Aedes aegypti, we found 1-hydroxy-2-methyl anthraquinone (1) to have good larvicidal activity. Extracts of the roots of Morinda citrifolia were also found to be larvicidal.